PARAMETER OPTIMIZATION AND VIRTUAL SCREENING INDONESIAN HERBAL DATABASE AS HUMAN IMMUNODEFICIENCY VIRUS -1 INTEGRASE INHIBITOR USING AUTODOCK AND VINA - Yanuar, Arry; Syahdi, Rezi Riadhi; Aryati, Widya Dwi (International Journal of Applied Pharmaceutics, 2017)
Objective: Human immunodeficiency virus (HIV-1) is a virus that causes acquired immunodeficiency syndrome, a disease considered to be one of the most dangerous because of its high mortality, morbidity, and infectivity. The emergence of mutant HIV strains has led treatment to target protease as reverse transcriptase and integrase enzyme become less effective. This study aims to provide knowledge about the potential of HIV-1 integrase inhibitors for use as guiding compounds in the development of new anti-HIV drugs. Methods: This study used AutoDock and AutoDock Vina for virtual screening of the Indonesian herbal database for inhibitors of HIV-1 integrase and is validated using a database of the directory of useful decoys. Optimization was accomplished by selecting the grid size, the number of calculations, and the addition of two water molecules and a magnesium atom as cofactor. Results: This study determined that the best grid box size is 21.1725×21.1725×21.1725 in unit space size (1 unit space equals to macromolecules 1Ǻ), using AutoDock Vina with EF and AUC values, 3.93 and 0.693, respectively. Three important water molecules have meaning in molecular docking around the binding pocket. Conclusions: This study obtained the top ten ranked compounds using AutoDock Vina. The compounds include: Casuarinin; Myricetin-3-O-(2'',6''- di-O-α-rhamnosyl)-β-glucoside; 5,7,2',4'-tetrahydroxy-6,3'-diprenylisoflavone 5-O-(4''-rhamnosylrhamnoside); myricetin 3-robinobioside; cyanidin 3-[6-(6-ferulylglucosyl)-2-xylosylgalactoside]; mesuein, cyanidin 7-(3-glucosyl-6-malonylglucoside)-4'-glucoside; kaempferol 3-[glucosyl-(1→3)- rhamnosyl-(1→6)-galactoside]; 3-O-galloylepicatechin-(4-β→8)-epicatechin-3-O-gallate; and quercetin 4'-glucuronide.